2011
DOI: 10.1080/00220970903292900
|View full text |Cite
|
Sign up to set email alerts
|

Being LabeledNerd: Factors That Influence the Social Acceptance of High-Achieving Students

Abstract: The present investigation addresses the question of whether certain factors can protect high-achieving students at risk for being labeled a nerd against devaluation. In 2 studies, 125 and 317 students from Grade 8 evaluated vignettes describing average students and students who were called "nerds." Results indicate that being modest about good grades, being engaged in sports, and being sociable led to higher liking. In students who were labeled nerds, but not in average students, display of effort led to less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 56 publications
(81 reference statements)
1
25
2
3
Order By: Relevance
“…However, conscientiousness, in particular, is associated with effort and studiousness, whereas openness is associated with ability (Costa & McCrae, ; Trautwein et al, ). Our results that indicated that students who are labelled as Strebers are more conscientious than others in their class support findings that emphasise the negative perception of effort by peers (Juvonen & Murdock, ; Landsheer et al, ; Rentzsch et al, ). However, as we did not assess intelligence or effort per se , it would be relevant to include other objective measures of ability or effort aside from academic achievement in future research and to investigate their predictive values in the process of the labelling.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, conscientiousness, in particular, is associated with effort and studiousness, whereas openness is associated with ability (Costa & McCrae, ; Trautwein et al, ). Our results that indicated that students who are labelled as Strebers are more conscientious than others in their class support findings that emphasise the negative perception of effort by peers (Juvonen & Murdock, ; Landsheer et al, ; Rentzsch et al, ). However, as we did not assess intelligence or effort per se , it would be relevant to include other objective measures of ability or effort aside from academic achievement in future research and to investigate their predictive values in the process of the labelling.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have shown that students whose academic success is due to effort are regarded less positively than students whose academic success is due to high ability (Juvonen & Murdock, , ; Tannenbaum, ). In a similar vein, Pelkner et al () showed that it is the studiousness of students in particular that is evaluated negatively by peers (see also Rentzsch et al, ; van der Linden, Scholte, Cillessen, Nijenhuis, & Segers, ). Because conscientiousness is characterised by academic orientation and academic effort, whereas openness is characterised by academic orientation and academic abilities, we assumed that being labelled a Streber would be related to high conscientiousness but not to openness.…”
Section: Personality and Being Labelledmentioning
confidence: 93%
See 1 more Smart Citation
“…U okviru dimenzije socijalni status i popularnost pojavljuju se opisi koji se odnose na fizički izgled (spretni, privlačni, sportski tipovi, lepi) i socijalne veštine (komunikativni, druželjubivi) koje jednu osobu mogu činiti manje ili više popularnom u društvu. Dobijeni rezultati potvrđuju i ranije nalaze koji upućuju na to da su socijalne (ne)kompetencije i fizička (ne)aktivnost i (ne)atraktivnost bitni aspekti stereotipa o štreberima (Eicher, Baizerman, & Michelman, 1991;England & Petro, 1998;Green & Ashmore, 1998;Kinney, 1993;Pelkner & Boehnke, 2003;Rentzsch, Schröder-Abé, & Schütz, 2013;Rentzsch, Schütz, & Schröder-Abé, 2011). Međutim, interesantno je to u da u našem kontekstu ove karakteristike nisu dominantno obeležje štrebera -štaviše, možemo reći da štreberinisu ni naročito popularni ni nepopularni.…”
Section: Diskusijaunclassified
“…Rezultati su pokazali da skromnost u pogledu dobrih ocena, bavljenje sportom i druželjubivost vode ka pozitivnijoj oceni od strane vršnjaka, čak i kada su u vinjeti prikazani učenici eksplicitno označeni kao štreberi. Dodatno, učenici označeni kao štreberi bili su pozitivnije procenjeni ukoliko su prikazani kao druželjubivi, čak i ukoliko se nisu bavili sportom (Rentzsch, Schütz, & Schröder-Abé, 2011). Ipak, bitno je naglasiti da su sva istraživanja Rentzschove korelacione studije koje ne omogućavaju izvođenje zaključka o tome da li je stereotip štrebera uzrok ili posledica, odnosno da li osobe koje su okarakterisane kao štreberi razvijaju set osobina koji dalje potvrđuje i produbljuje pripisani stereotip ili zaista samo određeni profil uspešnih učenika dobija ovakvu etiktu.…”
unclassified